Analisis Kelayakan Finansial Usaha Bakso Jamur Sawit (Volvariella Volvacea) di Kabupaten Sanggau - Yuni Selvianti Sari; Ahmad Mustangin; Marselus Hendro (Publikasi Indonesia, 2022)
Oil palm mushroom (Volvariella volvacea) is able to grow in empty bunches (tankos) of oil palm (Elaeis guineensis Jacq). This mushroom is commonly consumed, especially by people in Sanggau Regency, West Kalimantan. Palm mushrooms can be a variety of processed products, one of which is meatballs. The purpose of this study was to determine the financial feasibility of the oil palm mushroom (Volvariella volvacea) meatball business in Sanggau Regency and whether or not this business was feasible to run. The method stages in this research include literature study and the manufacture of oil palm mushroom meatballs, data collection through the questionnaire method, and financial feasibility analysis including BEP, R/C Ratio, IRR, ROI, and PP. The results of the respondent's assessment, as a whole, indicate that this oil palm mushroom meatball is feasible to sell with a financial analysis of the feasibility of the oil palm mushroom meatball business, with a BEP value of Rp. 5.368.00, BEP receipt of Rp. 235,294.00, BEP units are 29 units. The value of R/C ratio is 1.4, IRR is 47%, ROI is 29%, and PP is for 1 month. The conclusion from this research is that this business is feasible to run.